1999
DOI: 10.1093/ije/28.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of child deaths due to drowning in Matlab, Bangladesh

Abstract: A substantial proportion of child deaths could be averted if parents and other close relatives paid more attention to the safety of children. The Child Health Programme of the Ministry of Health and Family Welfare of Bangladesh should develop health education programmes for villagers alerting them to the dangers of drowning and measures to prevent it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
81
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 4 publications
13
81
3
Order By: Relevance
“…(2). In accordance with the literature, both of presented cases were in the first year of their lives and male (7,10,11).…”
Section: öZetsupporting
confidence: 86%
“…(2). In accordance with the literature, both of presented cases were in the first year of their lives and male (7,10,11).…”
Section: öZetsupporting
confidence: 86%
“…Previous studies have reported that socioeconomic status (e.g., household income) is one of the key indicators strongly associated with children's swimming skill (Irwin et al, 2009;Rahman et al, 2006). While socioeconomic status was related, this study and another from Bangladesh found that guardians' educational levels were not associated with children's reported swimming skill (Ahmed, Rahman, & Ginneken, 1999). This could be explained because there was lack of infrastructure such as swimming pools, swimming instructors, or swim programs in rural areas; therefore, children could not access swimming lessons.…”
Section: Discussioncontrasting
confidence: 67%
“…In addition, we identified new factors, such as attending a school with a pool and having a self-reported life-threatening submersion experience. While we found that guardians estimated that boys had higher swimming skill compared with girls, previous studies have indicated that boys also experience higher rates of drowning (Ahmed et al, 1999;Fang et al, 2007;Peden & McGee, 2003;Quan & Cummings, 2003;Rahman et al, 2006;Sitthi-amorn et al, 2006). One explanation for these finding is that males may have a greater exposure to aquatic activities or participate in higher risk aquatic situations (Gilchrist, Sacks, & Branche, 2000;Howland et al, 1996).…”
Section: Discussioncontrasting
confidence: 60%
“…Interestingly, the number, type, and age of family members seem to relate to the incidence of drowning (e.g., Ahmed, Rahman, & van Ginneken, 1999;Byard, de Koning, Blackbourne, Nadeau, & Krous 2001;Kaufman, 2005). Certain occupations might be more prone to risk of drowning due to the nature of the work (e.g., stunt men and seamen; Piët, 1987;Rafnsson, Gunnar, & Dottir, 1993;Bravo 2, 2007).…”
mentioning
confidence: 99%